Survei Tingkat Kebugaran Jasmani Siswa Ekstrakurikuler Futsal SMAN 2 Batu - Mario Bagus Ramadhan Agianto; Fahrial Amiq; Zihan Novita Sari (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
Physical fitness is a must for everyone. Maintaining physical fitness can help one's ability to perform physical activities successfully and efficiently without becoming overly tired. The purpose of this research is to ascertain and evaluate the physical fitness level of SMAN 2 Batu futsal extracurricular players. This study aims to determine and assess the level of physical fitness of futsal extracurricular participants of SMAN 2 Batu. This study used a descriptive quantitative survey design. The sample taken was all the population who participated in extracurricular activities totaling 70 futsal extracurricular students. This research instrument used the Indonesian Physical Fitness Test (TKJI)16-19 years and non-test instruments in the form of observation. Data were analyzed using descriptive statistics. The results of the research on the survey of the level of physical fitness in futsal extracurricular students at SMAN 2 Batu, namely from a total of 70 student participants, there were 8 students who were in the good category with a percentage of 11.42%, 38 students were in the moderate category with a percentage of 54.28%, 21 students were in the poor category with a percentage of 30%, and 3 students were in the very poor category with a percentage of 4.28%. Based on the results of the study, it can be concluded that the level of physical fitness of students participating in extracurricular futsal at SMAN 2 Batu is in the moderate category, the hope of this research is that students are more aware of maintaining physical fitness and can be motivated to improve it.